Introduction to materials management - Arnold, J. R. Tony, 1928-2012; Chapman, Stephen N., ....-; Clive, Lloyd M., ....- (Boston : Pearson, 2012)
Introduction to Materials Management, Seventh Edition covers all the essentials of modern supply chain management, manufacturing planning and control systems, purchasing, and physical distribution. Clearly written and exceptionally user-friendly, its content, examples, questions, and problems lead students step-by-step to mastery. This edition's extensive updates include: new techniques, technology, and case studies; reorganized and expanded coverage of lean production and JIT manufacturing; new information on sustainability and "green" production; use of INCOTERMS for global supply chains; revised end-of-chapter problems, and more. Widely adopted by colleges and universities worldwide, this is the only APICS-listed reference text for the Basics of Supply Chain Management (BSCM) CPIM certification examination.